AKUNTABILITAS DAN TRANSPRANSI PERTANGGUNGJAWABAN PEMERINTAH DAERAH DALAM RANGKA MEWUJUDKAN PEMERINTAHAN YANG BAIK DI KOTA MATARAM - Ismail Ismail (Sekolah Tinggi Ilmu Ekonomi AMM, 2016)
In the reform era, the government has issued two packages of legislation on regional autonomy, the first is the Law No. 22 athun 1999, Act No. 25 of 1999 on Financial Balance between Central and Local Government and the Second Law Number 32 Year 2004 and Act No. 33 of 2004 on Regional Government. Act is called the second revision of the Act is the so-called first-Undan. Package regional autonomy policy is the first on the issuance of Law No. 22 of 1999, many people considered that the release of the regional autonomy policy is a turning point for the implementation of regional autonomy that is more democratic than the regional autonomy policy previously regulated by Law No. 5 of 1974 is considered to be very centralized. This study aims to investigate the implementation of accountability of governance in Mataram, implementation or application of the principles of accountability and transparency of governance as well as any obstacles encountered in transaparasni implement its principles of accountability and governance in order to realize a good pemrintahan in Mataram. This research is a normative law in support of empirical data, the main ingredient is the literature or referred to secondary data, while the field data needed to obtain primary data and only be used as reference material or supplementary. Data collected are interviews with some of the speakers who are competent and know the problems studied. Results were analyzed using qualitative methods. The findings showed that based on PP. Nomo 3 of 2007, there are 3 (three) form of government responsibility in the governance and development of Regional Government that report by the Mayor to the Government, Report Description governments accountable to the Parliament and Government Accountability report information to the public. Implementation of accountability and transparency in the accountability of city government to realize good governance, have not been followed by an evaluation by the higher levels of government for the delivery LPPD, delivery LKPJ not accompanied with the calculation of the budget, discussion or assessment of accountability to the area by the Parliament tends to be political and msyarakat less watch LPPD head of the region that have been submitted. For accountability and transparency can be realized in conformity with accounting standards, the future should be the accountability reports of local government need to be evaluated by the higher levels of government, parliament and community participation to provide a response to and an objective assessment of the report pertanggungjawan head of the area, so at The trouble future governance will be more transparent and accountable in efforts to achieve good governance, clean and accountable